Stress‐inducible phosphoprotein 1 has unique cochaperone activity during development and regulates cellular response to ischemia via the prion protein. Issue 9 (31st May 2013) - Beraldo, Flavio H.; Soares, Iaci N.; Goncalves, Daniela F.; Fan, Jue; Thomas, Anu A.; Santos, Tiago G.; Mohammad, Amro H.; Roffé, Martin; Calder, Michele D.; Nikolova, Simona; Hajj, Glaucia N.; Guimaraes, Andre L.; et al.
Abstract : Stress‐inducible phosphoprotein 1 (STI1) is part of the chaperone machinery, but it also functions as an extracellular ligand for the prion protein. However, the physiological relevance of these STI1 activities in vivo is unknown. Here, we show that in the absence of embryonic STI1, several Hsp90 client proteins are decreased by 50%, although Hsp90 levels are unaffected. Mutant STI1 mice showed increased caspase‐3 activation and 50% impairment in cellular proliferation. Moreover, placental disruption and lack of cellular viability were linked to embryonic death by E10.5 in STI1‐mutant mice. Rescue of embryonic lethality in these mutants, by transgenic expression of the STI1 gene, supported a unique role for STI1 during embryonic development. The response of STI1 haploinsufficient mice to cellular stress seemed compromised, and mutant mice showed increased vulnerability to ischemic insult. At the cellular level, ischemia increased the secretion of STI1 from wild‐type astrocytes by 3‐fold, whereas STI1 haploinsufficient mice secreted half as much STI1. Interesting, extracellular STI1 prevented ischemia‐mediated neuronal death in a prion protein‐dependent way. Our study reveals essential roles for intracellular and extracellular STI1 in cellular resilience.—Beraldo, F. H., Soares, I. N., Goncalves, D. F., Fan, J., Thomas, A. A., Santos, T. G., Mohammad, A. H., Roffe, M., Calder, M. D., Nikolova, S., Hajj, G. N., Guimaraes, A. N., Massensini, A. R., Welch, I., Betts, D. H., Gros, R., Drangova, M., Watson, A. J., Bartha, R., Prado, V. F., Martins, V. R., and Prado, M. A. M., Stress‐inducible phosphoprotein 1 has unique cochaperone activity during development and regulates cellular response to ischemia via the prion protein. FASEB J. 27, 3594–3607 (2013). www.fasebj.org